UPAYA MENINGKATKAN KEMAMPUAN PROBLEM SOLVING PADA MATA PELAJARAN IPA DENGAN MODEL PROJECT BASED LEARNING SISWA KELAS V - Nidya Chandra Muji Utami; Aisyah Nurlaila Sari Dewi; Aghniya Alip Puteri; Engga Dallion (JS (JURNAL SEKOLAH), 2023)
Abstract: Through the use of the project based learning approach, this research aims to enhance the problem solving skills of fifth-grade students at SD Ar-Rahman Motik. The Kemmis & McTaggart model was used in this research, which was conducted over the course of two cycles. Each cycle includes the four processes of planning, implementing out, observing, and reflecting. This research's participants included 23 members of class VB SD Ar-Rahman Motik. The even semester of the academic year 2022–2023 was used for this research. Through testing, observation, and interviews, research data was obtained. The results showed that there was an increase in students' problem solving abilities through the application of the Project Based Learning model where the pre-cycle results showed an average of 67.11% in cycle I increased to 85.53% and increased again in cycle II to 88.25%. The conclusion from the results of the analysis is that the Project Based Learning (PjBL) model in science learning can improve the problem solving skills of VB class students at SD Ar-Rahman Motik.Keyword: Project Based Learning, Problem Solving, ScienceAbstrak: Melalui penggunaan pendekatan pembelajaran project based learning, penelitian ini bertujuan untuk meningkatkan kemampuan problem solving siswa kelas V SD Ar-Rahman Motik. Model Kemmis & McTaggart digunakan dalam penelitian ini yang dilakukan selama dua siklus. Setiap siklus meliputi empat proses, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah 23 orang anggota kelas VB SD Ar-Rahman Motik. Penelitian ini dilaksanakan pada semester genap tahun akademik 2022–2023. Data penelitian diperoleh melalui tes, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa terjadi peningkatan kemampuan problem solving siswa melalui penerapan model project based learning dimana hasil prasiklus menunjukkan rata-rata 67,11% pada siklus I meningkat menjadi 85,53% dan meningkat lagi pada siklus II menjadi 88,25 %. Kesimpulan dari hasil analisis adalah model Project Based Learning (PjBL) dalam pembelajaran IPA dapat meningkatkan kemampuan problem solving siswa kelas VB di SD Ar-Rahman Motik.Kata Kunci: Project Based Learning, Problem Solving, IPA